NUTRIENT DIGESTIBILITY OF RATION CONTAINING DIFFERENT PROTEIN AND ENERGY LEVEL ON BALI CATTLE HEIFERS - F. D., Valentina; Suarna, I W.; Suryani, N. N. (Jurnal Peternakan Tropika; Vol 6 No 1 (2018): Vol. 6 No. 1 (2018), 2018)
This study aims to determine the effect of different protein and energy level on nutrient digestibility of bali cattle heifers. This research has been conducted in Farm cattle at Belok Sidan village Petang District, Badung Regency for 3 months. A total of 12 bali cattle heifers  used in this study were divided into three groups based on body weight. The treatments consisted of four types of rations, a ration containing 12% crude protein and 2000 kcal ME/kg (treatment A), 13% crude protein and 2100 kcal ME/kg (treatment B), 14% crude protein and  2200 kcal ME/kg (treatment C), and 15% crude protein and 2300 kcal ME/kg (treatment D). The experimental design used was a randomized block design (RCBD). The observed variables were dry matter digestibility, organic matter digestibility, crude protein digestibility, ether extract digestibility and crude fiber digestibility. The results showed that fed ration with different protein and energy content has not significant different (P>0.05) of digestibility of dry matter, organic matter and crude fiber respectively with with values ??of 65.77-71.17%; 67,57-72,60%; and 53.13-54.32%. While for variable of crude protein digestibility and extract ether digestibility, fed rations with different protein and energy content yielded significantly different values ??(P<0.05). Crude protein digestibility and ether extract ether digestibility of treatment D were 23,64% and 16,56% higher respectively than treatment A. Based on the result of this study it was concluded that the increase of protein content of ration from 12% to 15% and metabolized energy from 2000 to 2300 kcal/kg does not affect the digestibility of dry matter, organic matter and crude fiber, but can improve the digestibility of crude protein and ether extract of bali cattle heifers.  Keyword: protein and energy, nutrient digestibility, bali cattle heifers